Extraction, purification, in vitro antioxidant and cytoprotective ability of oligostilbenes from paeonia seeds threshing residues - Xiao-Jun Li; Heng-hui Zhang; Yong-ping Xu; Shu-ying Li; Na Li; Qing-ye Liu; Fang Zhang (PLoS ONE, 2025)
Objective Oligostilbenes, which have been associated with multiple biological activities, are a kind of oligomeric resveratrol compound and widely exist in Paeonia seeds threshing residues. The re-use of the Paeonia seeds threshing residues as value-added materials is, not only cost-effective, but also environmentally beneficial. It is therefore important to develop a high-efficiency method for extraction of oligostilbenes. Methods In this investigation, different extraction methods (soxhlet extraction, high temperature and pressure extraction, cold soaking extraction, heat reflux extraction, and ultrasonic extraction) were used to extract oligostilbenes from Paeonia seeds threshing residues. By comparing the extraction yield and in vitro antioxidant ability of oligostilbenes obtained from different extraction ways, the optimal extraction technology of Paeonia seeds threshing residues oligostilbenes was selected. The macroporous resin was used to purify oligostilbenes crude extract samples, and the purification conditions were determined. The protective effect of purified oligostilbenes on oxidative damage of MODE-K cells was evaluated. Results Ultrasonic extraction with ethanol (UA-E) possessed the highest extraction yield of oligostilbenes, and the extraction yield was (3.45 ± 0.07)%. The oligostilbenes extracts obtained by different extraction methods had scavenging ability on DPPH· and ABTS+·, and UA-E showed relatively stronger scavenging ability at different concentration levels. The best resin for purifying oligostilbenes was X-5, and the adsorption and desorption rates were (93.12 ± 0.16)% and (91.33 ± 0.40)%, respectively. The optimal adsorption/desorption conditions were sample loading rate of 2 BV/h, ethanol concentration of 70%, and elution flow rate of 1.0 BV/h. There was a dose-response relationship between the scavenging ability of purified oligostilbenes on DPPH· and ABTS+· and the concentration of the samples. The oligostilbenes could relieve the oxidation effect of hydrogen peroxide (H2O2) on MODE-K cells, and enhance the protection of MODE-K cells by regulating the relative SOD activity, MDA, and ROS production. Conclusion This research lays a theoretical foundation and scientific reference for the extraction, purification and application of Paeonia seed threshing residues in food and medicine.